2013
DOI: 10.1007/s10565-013-9249-y
|View full text |Cite
|
Sign up to set email alerts
|

Olaquindox-induced apoptosis is suppressed through p38 MAPK and ROS-mediated JNK pathways in HepG2 cells

Abstract: We investigated mitogen-activated protein kinase (MAPK) pathways as well as reactive oxygen species (ROS) in olaquindox-induced apoptosis. Exposure of HepG2 cells to olaquindox resulted in the phosphorylation of p38 MAPK and c-Jun N-terminal kinases (JNK). To confirm the role of p38 MAPK and JNK, HepG2 cells were pretreated with MAPKs-specific inhibitors prior to olaquindox treatment. Olaquindox-induced apoptosis was significantly potentiated by the JNK inhibitor (SP600125) or the p38 MAPK inhibitor (SB203580)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…CAT partially reversed the ROS levels and partially alleviated DNA damage when HeLa cells, HepG2 cells, primary pig hepatocytes, and primary chicken embryo hepatocytes were incubated with MEQ (50 lg/mL) and CAT (50 U), suggesting that CAT could protect against apoptosis, cellular DNA damage induced by MEQ in part, via ROS down-regulation . In addition, the combination of SOD (500 U/mL) and CAT (500 U/mL) significantly decreased ROS production and the levels of phosphorylation of JNK induced by OLA (800 lg/mL) in HepG2 cells, indicating that SOD and CAT might inhibit cell apoptosis via ROS-JNK pathway (Zhao et al, 2013). Zhang et al revealed that vitamin C (100 lM) increased the survival rates of HepG2 cells of QCT groups (80 and 320 lM), whereas vitamin E (10 and 100 lM) could not (Zhang et al, 2014).…”
Section: Prevention Of Qdnos-mediated Oxidative Stressmentioning
confidence: 93%
See 4 more Smart Citations
“…CAT partially reversed the ROS levels and partially alleviated DNA damage when HeLa cells, HepG2 cells, primary pig hepatocytes, and primary chicken embryo hepatocytes were incubated with MEQ (50 lg/mL) and CAT (50 U), suggesting that CAT could protect against apoptosis, cellular DNA damage induced by MEQ in part, via ROS down-regulation . In addition, the combination of SOD (500 U/mL) and CAT (500 U/mL) significantly decreased ROS production and the levels of phosphorylation of JNK induced by OLA (800 lg/mL) in HepG2 cells, indicating that SOD and CAT might inhibit cell apoptosis via ROS-JNK pathway (Zhao et al, 2013). Zhang et al revealed that vitamin C (100 lM) increased the survival rates of HepG2 cells of QCT groups (80 and 320 lM), whereas vitamin E (10 and 100 lM) could not (Zhang et al, 2014).…”
Section: Prevention Of Qdnos-mediated Oxidative Stressmentioning
confidence: 93%
“…Li et al revealed that OLA (1, 2, 3 and 4 lM/mL) increased the apoptosis rate of renal tubular epithelial cells (HK-2 cells) followed by ROS generation, suggesting that OLA might cause renal toxicity through the apoptosis-associated toxicity pathway via oxidative stress . After the exposure of HepG2 cells to OLA (800 lg/mL) for 24 or 48 h, OLA led to significant apoptosis (Zhang et al, 2011;Zhao et al, 2013;Zou et al, 2011). Similarly, when HepG2 cells were incubated with QCT, DQCT and MQCA for 24 h, QCT (10, 20, 30 and 40 lM) resulted in significant apoptosis whereas 80 lM of DQCT and MQCA did not cause apoptosis, indicating that the N!O group plays important roles in the toxicity of QdNOs (Zhang et al, 2015).…”
Section: Apoptosis and Cell Cyclementioning
confidence: 97%
See 3 more Smart Citations